Model of diffusive interaction between two-phase alloys with explicit fine-tuning of the morphology evolution. (15th April 2016) - Danielewski, Marek; Gusak, Andriy; Bożek, Bogusław; Zajusz, Marek
Abstract: Interdiffusion between two-phase ternary alloys is described analytically and numerically with self-consistent account of thermodynamical constraints and of morphology evolution. At that, growth/shrinking of minority phase precipitates and their flow with parent phase lattices are taken into account. Description scheme is multiscale (actually – double-scaled): it uses both coarsened scale for overall concentrations and phases redistribution, and it uses fine-scale for description of growth or shrinking of each precipitate. Natural constraints on the effective interdiffusivity matrices in coarsened scale are formulated (zero determinant). We show characteristic zigzag-type diffusion paths, horn-like paths and additional regimes with single-phase sublayers. Model enables to trace the history of deviations from the Local Equilibrium condition in both matrix phases and enables to predict the redistribution of precipitates in both matrix phases. Graphical abstract: